The role of the crystallo-chemical factor in the evaluation and improvement of the nanomodification efficiency of mortar and concrete - Pushkarova, Katerina; Gonchar, Olga; Kaverin, Konstantin (IOP Conference Series: Materials Science and Engineering, 2019)
The article presents a new approach to the control of the processes of structure formation of binder systems, taking into account the achievements of nanotechnologies. The possibilities of managing the structure of the material at the nanoscale and the micro-level by introducing primary nanoscale additives or forming nanoscale objects in the bulk of the material are considered. The peculiarities of contact zone formation and microstructure of artificial stone based on nanomodified Portland cement and alkaline binder systems are investigated. The role of the crystallo-chemical factor and its influence on the strength formation of all levels of concrete structure are shown. It is proved that when using micro silica modifying additives, their efficiency at the micro level is higher than at the meso- and macrolevels. At the same time, the modification of the binding systems by artificial zeolites provides a more pronounced effect in concrete at the macro-level – due to the crystallo-chemical similarity of additives, products of hydration and minerals of the aggregate. Taking into account the crystal-chemical similarity of the new formation opens new possibilities for the choice of nano additives, considering not only the principle and nature of their action at the level of nanoscale and microstructure, but also the influence on the peculiarities of the formation of the contact zone at the meso- and macro-levels, which will have a decisive influence not only on the strength, but also on the special properties of concrete.
Keywords: nanotechnologies; contact zone; artificial zeolites; crystal-chemical similarity; alkaline binder systems; рortland cement